The Role of Primary Health Care in the Prevention of Noncommunicable Diseases - Indah S Widyahening (Faculty of Medicine, Public Health, and Nursing, 2019)
Noncommunicable diseases (NCDs) currently cause more deaths than all other causes combined. Cardiovascular diseases, cancer, chronic respiratory diseases and diabetes are the four major NCDs that are responsible for 82% of NCD deaths. Approximately 42% of all NCD deaths globally occurred before the age of 70 years; 48% of NCD deaths in the low- and middle-income countries and 28% in high-income countries were in individuals aged under 70 years.(1) Because of its chronic nature and the complications that arisen, NCDs bring devastating social, economic and public health impact. The management of its various long-term complications accompanied by the typical existence of multimorbidity will give rise to an increased complexity of care in the future. Aging, improved medical therapies, demographic transition, life-style changes, globalization and urbanization are factors that are contributing to the increased prevalence, severity and complexity of NCDs.........